Historia Apollonii regis Tyri a fourteenth-century version of a late antique romance : edited from Vatican City, Biblioteca Apostolica Vaticana, MS Vaticanus latinus 1961 - Robins, William 1964- (Centre for Medieval Studies by the Pontifical Institute for Mediaeval Studies, 2019)
"The Historia Apollonii regis Tyri provided medieval Europe with one of its most popular and influential narratives. The tale incorporates many literary features characteristic of the ancient Hellenistic novel, but differs markedly from its Greek predecessors: its narrative is presented in condensed fashion, its description of characters and events straightforwardly functional, and the style of its Latin simple. While these features make the Historia Apollonii an oddity among the ancient novels, they contributed to the appeal the story held for later readers and writers in medieval Europe. The aim of this edition is to provide a text of the Latin Historia Apollonii as a reader from the later Middle Ages might have encountered it: as it appears in Vatican City, Biblioteca Apostolica Vaticana, Vat. lat. 1961, a manuscript written in Italy in the middle of the fourteenth century."--
Keywords: Historia Apollonii regis Tyri; Biblioteca apostolica Vaticana / Manuscript / Vat. lat. 1961; Apollonius of Tyre (Fictitious character) / Romances; Literature, Medieval / Roman influences; Romances, Latin (Medieval and modern); Biblioteca apostolica Vaticana / Manuscrit / Vat. lat. 1961; Apollonius de Tyr (Personnage fictif) / Romans, nouvelles, etc; Littérature médiévale / Influence romaine; Roman courtois latin médiéval et moderne; Apollonius of Tyre (Fictitious character); Romances; Quelle